Experiences of Swedish Parents Seeking Social Services Support for Their Adult Children With Drug Addiction - Richert, Torkel; Svensson, Bengt; Johnson, Björn ; 0000-0002-1601-2706 (Journal of the Society for Social Work and Research, 2021)
Objective: Family members of a person with drug addiction often experience negative impacts on their lives and face barriers to seeking professional support. More knowledge is needed about such barriers so they can be reduced. This article examines the help-seeking experiences of parents of adult children with drug addiction, a group that has received little attention in research. Method: We conducted in-depth interviews with 32 parents of adult children with drug addiction in Sweden. Results: Parents described problems in encounters with social services and barriers to adequate support for their children. On a psychological level, they described feelings of shame and guilt, negative views of social services, and fear of stigma and loss of control that were barriers to seeking professional support. On an interpersonal level, barriers to help were connected to problems in the interaction among parents, children, and social services. On a structural level, barriers pertain to deficiencies in the availability and quality of support measures, inadequate cooperation between authorities, and a shift in responsibility from the state to the individual and the family. Conclusions: Parents of children with drug addiction are a vulnerable group that often experience problems in their contacts with authorities. A more collaborative approach by social services may abate parents’ self-blame and concern and may strengthen their role in their children’s treatment process.
2025-03-05T18:36:31.013+01:00
Keywords: Sociology and Political Science; Social Sciences (miscellaneous); Social Work; Socialt arbete